Transformasi Sampah Rumah Tangga Berbasis Maggot BSF Sebagai Inovasi Pemberdayaan Karang Taruna untuk Kemandirian Ekonomi di Cimahi Utara - Herdiani, Leni; Sustariyah, Sri; Rohimat, R. Ismet; Nur'aeni, Silvi Fitrian Sri; Milarantika, Dhila (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
Household waste management remains a major issue in urban areas, including in North Cimahi District which produces more than 250 tons of waste per day, with organic waste comprising up to 60%. Most of this waste is still disposed of at the overcapacity Leuwigajah landfill, creating serious environmental, health, and social problems. This community service program aims to provide an innovative solution through the transformation of organic waste into Black Soldier Fly (BSF) maggots while empowering youth organizations (Karang Taruna) to enhance economic self-reliance. The program was carried out through coordination, technical training, business management mentoring, the application of appropriate technology (kitchen waste chopper and dried maggot milling machine), as well as product marketing strategies. The results indicate that the partners’ capacity in managing organic waste has significantly improved, producing fresh, dried, and powdered maggot products with higher economic value. Social impact is evident in the active involvement of Karang Taruna members throughout all program stages and the increasing awareness of the local community regarding waste separation. Economic impact is reflected in the establishment of a new maggot-based business unit with potential for additional income. Meanwhile, the environmental impact is demonstrated by the reduction in the volume of organic waste sent to the landfill. In conclusion, community-based BSF maggot cultivation not only addresses household waste problems but also fosters the development of a sustainable circular economy ecosystem. This model has strong potential to be replicated in other areas with similar characteristics as a strategy for waste management and youth empowerment.